2007
DOI: 10.1007/s10571-007-9206-5
|View full text |Cite
|
Sign up to set email alerts
|

Huntington’s Disease and Mitochondrial DNA Deletions: Event or Regular Mechanism for Mutant Huntingtin Protein and CAG Repeats Expansion?!

Abstract: The mitochondrial DNA (mtDNA) may play an essential role in the pathogenesis of the respiratory chain complex activities in neurodegenerative disorders such as Huntington's disease (HD). Research studies were conducted to determine the possible levels of mitochondrial defect (deletion) in HD patients and consideration of interaction between the expanded Huntingtin gene as a nuclear gene and mitochondria as a cytoplasmic organelle. To determine mtDNA damage, we investigated deletions based in four areas of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 36 publications
0
29
0
Order By: Relevance
“…Recent research has revealed multiple alterations in mitochondria, in HD progression and pathogenesis, including: (i) reduced enzymatic activity in several components of oxidative phosphorylation, including complexes II, III and IV of the electron transport chain, in HD postmortem brains and HD mouse models [2224], suggesting that mitochondria are involved in HD pathogenesis; (ii) low mitochondrial ATP and decreased mitochondrial ADP uptake in HD knock-in striatal cells and lymphoblasts from patients with HD, revealing expanded polyglutamine repeats [25]; (iii) defective calcium-induced mitochondrial permeability in HD cell lines and HD mice (reviewed in [26]); (iv) mHtt-induced defective mitochondrial trafficking in HD primary neurons [15,17,18,27]; (v) age-dependent mitochondrial (mt)DNA damage and mtDNA deletions in HD-affected neurons [28,29]; and (vi) biochemical, confocal and electron microscopy studies revealed structurally damaged mitochondria with broken cristae, and small and round mitochondria in HD-affected neurons [1821] (Figure 1). …”
Section: Mitochondrial Abnormalitiesmentioning
confidence: 99%
“…Recent research has revealed multiple alterations in mitochondria, in HD progression and pathogenesis, including: (i) reduced enzymatic activity in several components of oxidative phosphorylation, including complexes II, III and IV of the electron transport chain, in HD postmortem brains and HD mouse models [2224], suggesting that mitochondria are involved in HD pathogenesis; (ii) low mitochondrial ATP and decreased mitochondrial ADP uptake in HD knock-in striatal cells and lymphoblasts from patients with HD, revealing expanded polyglutamine repeats [25]; (iii) defective calcium-induced mitochondrial permeability in HD cell lines and HD mice (reviewed in [26]); (iv) mHtt-induced defective mitochondrial trafficking in HD primary neurons [15,17,18,27]; (v) age-dependent mitochondrial (mt)DNA damage and mtDNA deletions in HD-affected neurons [28,29]; and (vi) biochemical, confocal and electron microscopy studies revealed structurally damaged mitochondria with broken cristae, and small and round mitochondria in HD-affected neurons [1821] (Figure 1). …”
Section: Mitochondrial Abnormalitiesmentioning
confidence: 99%
“…No mtDNA deletions have been found in SCA patients in this study. We have previously shown high frequencies of mtDNA deletions in HD and lower levels in Friedreich's ataxia [24,41] . These findings point to the existence of a complicated mechanism that directly corresponds to the type of protein involved and the related mechanism.…”
Section: Discussionmentioning
confidence: 94%
“…Involvement of nuclei and mitochondria in HD pathophysiology has been suggested (Sawa et al 1999). Banoei et al (2007) showed that huntington patients had higher mtDNA deletions than normal controls due to the presence of CAG repeats expansion (Banoei et al 2007). Furthermore, HD patients showed increased oxidative stress, together with higher amounts of deleted mtDNA and total mtDNA in peripheral leukocytes.…”
Section: Discussionmentioning
confidence: 99%